2017
DOI: 10.1542/peds.2016-2675
|View full text |Cite
|
Sign up to set email alerts
|

Health Risk Behaviors With Synthetic Cannabinoids Versus Marijuana

Abstract: BACKGROUND AND OBJECTIVES: Data are limited on the behavioral risk correlates of synthetic cannabinoid use. The purpose of this study was to compare the behavioral risk correlates of synthetic cannabinoid use with those among marijuana users.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 37 publications
0
34
0
Order By: Relevance
“…Seven cross-sectional studies were included in the review and are detailed in Table 3a. As shown, studies varied in study populations, ranging from those with psychosis following SC use (Altinas et al, 2016) to adult (Cohen et al, 2017;Gunderson et al, 2014) and adolescent cannabis users who have ever used SCs (Blevins et al, 2016) to high school students who have used SCs and NCs (Clayton et al, 2017). In addition, all studies acknowledged an overlap between NC and SC use, with those having used SCs having typically also using NC.…”
Section: Cross-sectional Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Seven cross-sectional studies were included in the review and are detailed in Table 3a. As shown, studies varied in study populations, ranging from those with psychosis following SC use (Altinas et al, 2016) to adult (Cohen et al, 2017;Gunderson et al, 2014) and adolescent cannabis users who have ever used SCs (Blevins et al, 2016) to high school students who have used SCs and NCs (Clayton et al, 2017). In addition, all studies acknowledged an overlap between NC and SC use, with those having used SCs having typically also using NC.…”
Section: Cross-sectional Studiesmentioning
confidence: 99%
“…From the studies by Bonar, Ashrafioun and Ilgen (2014) and Clayton et al, (2017) it appears that SC users are generally younger and more likely to be male than non-SC users. These two studies also reported on ethnicity and while one found that SC users were significantly more likely to be white (Bonar et al, 2014) the other found that they were less likely to be white (Clayton et al, 2017).…”
Section: Cross-sectional Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Most SCs' users are young men, many with a history of polysubstance use [24], housing problems or a history of arrests [46]. Recent studies indicate that students using SCs tend to engage in more risky behaviors than students who use marijuana alone [47].…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, multiple accounts claim that he kept smoking marijuana and started abusing other drugs and alcohol. During his arrest for the Charleston shooting, Roof told police officers that he abused drugs before committing such heinous act [5,25,26].…”
Section: Marijuana Violencementioning
confidence: 99%